Formation and speciation of haloacetamides and haloacetonitriles for chlorination, chloramination, and chlorination followed by chloramination. (January 2017) - Huang, Huang; Chen, Bo-Yi; Zhu, Zi-Ru
Abstract: The formation of haloacetamides (HAcAms) and haloacetonitriles (HANs) from a solution containing natural organic matter and a secondary effluent sample was evaluated for disinfection by chlorination, chloramination, and chlorination followed by chloramination (Cl2 NH2 Cl process). The use of preformed monochloramine (NH2 Cl) produced higher concentrations of HAcAms and lower concentrations of HANs than chlorination, while the Cl2 NH2 Cl process produced the highest concentrations of HAcAms and HANs. These results indicate that the Cl2 NH2 Cl process, which inhibited the formation of regulated trihalomethanes compared with chlorination, enhanced the formation of HAcAms and HANs. For disinfection in the presence of bromide, brominated dihaloacetamides and dihaloacetonitriles were formed, and the trends were similar to those observed for chlorinated species in the absence of bromide. The degrees of bromine substitution of dihaloacetamides and dihaloacetonitriles were highest for chlorination, followed by the Cl2 NH2 Cl process and then by the NH2 Cl process. For the Cl2 NH2 Cl process, HAN formation kept gradually increasing with prechlorination time increasing from 0 to 120 min, while HAcAm formation increased only until it reached a maximum at around 10–30 min. These results suggest that the prechlorination time could be reduced to control the formation of HAcAms and HANs. During chloramination, the formation of HAcAms and HANs was lower when using preformed NH2 Cl than when chloramines were formed in situ, with higher formation of HAcAms and HANs when chlorine was added before ammonia than vice versa for the secondary effluent; this finding suggests that preformed NH2 Cl could be used to inhibit the formation of HAcAms and HANs during chloramination. Highlights: The Cl2 –NH2 Cl process formed more haloacetamides (HAcAms) and haloacetonitriles (HANs) than the Cl2 and NH2 Cl processes. Bromine substitution factors (BSFs) of dihaloacetamides (DHAcAms) were higher than those of dihaloacetonitriles (DHANs). The order for the BSFs of DHAcAms and DHANs from highest to lowest was: Cl2 process, Cl2 –NH2 Cl process, and NH2 Cl process. The Cl2 +NH3 process formed more disinfection by-products than the NH3 +Cl2 process for in situ chloramination.